Histoarchitectural Alterations in Various Tissues of Poecilia sphenops Exposed Three Sub Lethal Concentrations of Atrazine - Vasanth, S; Vijayakumar, T Siva; Bupesh, G; Meenakumari, K; Buelah, J Jasmine (Asian Journal of Biological and Life Sciences)
Atrazine can affect normal physiological processes of many aquatic organisms, especially fish. In the current study, the Poecilia sphenops were exposed to 3 sub lethal concentrations 0.83ppm, 1.25ppm and 2.5ppm of atrazine and control also maintained simultaneously. Most histological changes were noticed in the group exposed to 1.25ppm and 2.5ppm. Hepatocytes show changes like wrinkled blood vessel, necrotic area, disintegrating acinar cell, cell debris, perivascular necrosis, vascular damage with swelling, Fragmented ova with abnormal shape and large number of early vitellogenic oocytes were observed in ovaries, the structural modifications in gill are edema, epithelial lifting, and thickening of the primary lamellar epithelium and fusion of secondary lamellae.
Keywords: Atrazine; Histoarchitectural; Poecilia sphenops; Sub Lethal Concentrations.; Tissues